Migración, ocupación y matrimonio: una aproximación a las relaciones de género de las parejas mixtas en España - Cortina, Clara; García, Thaís; Esteve, Albert (El Colegio de México A.C., 2009)
This article analyzes the condition of dual earner couples as a means of observing gender relations in the specific case of mixed unions within the context of the growing presence of international immigrants in Spain. To this end, the authors have simultaneously considered the position of these immigrant men and women in the labor and marriage markets. Using data from the Survey on the Active Population in Spain for the second quarter of 2007, they analyze conjugal homogamy and the occupational status of the spouses. Couples are classified according to whether both spouses are employed or only one. Multivariate methods of analysis are used to determine the probability that the different types of unions will have a single or double income. Differentiated analyses are undertaken according to the region of origin of the immigrant spouses (Latin Americans, West Europeans, East Europeans and Maghrebis).In a context of an increasing number of mixed marriages and the expansion of the double income model in couples, the main results show that in mixed unions, spouses are likely to be older and that there is a wide range of educational attainment. The likelihood of a double income also depends on the origin of the spouses. In other words, mixed unions are more or less equal in terms of gender (in terms of the spouse’s sex and origin) to the unions currently being formed by Spaniards.